2010
DOI: 10.1007/s00216-009-3431-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine profiles of Δ9-tetrahydrocannabinol and its metabolites 11-hydroxy-Δ9-tetrahydrocannabinol and 11-nor-9-carboxy-Δ9-tetrahydrocannabinol after cannabis smoking by male volunteers to estimate recent consumption by athletes

Abstract: Since 2004, cannabis has been prohibited by the World Anti-Doping Agency for all sports competitions. In the years since then, about half of all positive doping cases in Switzerland have been related to cannabis consumption. In doping urine analysis, the target analyte is 11-nor-9-carboxy-Delta(9)-tetrahydrocannabinol (THC-COOH), the cutoff being 15 ng/mL. However, the wide urinary detection window of the long-term metabolite of Delta(9)-tetrahydrocannabinol (THC) does not allow a conclusion to be drawn regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…In contrast, Brenneisen and colleagues [74] asked participants to smoke a cannabis cigarette containing 70mg 9 -THC, 25mg of which was estimated to have been inhaled. Mean plasma (SD) 9 -THC 5 minutes post inhalation was 20.9 (16.9) ng/ml.…”
Section: Doses and Pharmacokineticsmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, Brenneisen and colleagues [74] asked participants to smoke a cannabis cigarette containing 70mg 9 -THC, 25mg of which was estimated to have been inhaled. Mean plasma (SD) 9 -THC 5 minutes post inhalation was 20.9 (16.9) ng/ml.…”
Section: Doses and Pharmacokineticsmentioning
confidence: 94%
“…plasma levels are 2-3 times that of inhaled 9 -THC. This is especially true if participants self-titrate until they have reach their desired level of "high" [34,38], or in studies where unpleasant reactions such as anxiety or dysphoria are not reported [74].…”
Section: Doses and Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, OF THCCOOH could estimate plasma THCCOOH levels. Throughout the last decade, several studies have been carried out to determine PK parameters of cannabinoids in blood, plasma, or serum [16][17][18][19][20][21] in humans. Some other studies were performed with oral fluid only [22] or in tandem with serum [23] or plasma [11,24] with a limited number of ten participants in each study.…”
Section: Introductionmentioning
confidence: 99%
“…Profiling of illicit drugs has been performed for many target analytes which include cocaine [90], marijuana [91], heroin [92,93], and 3,4-methylenedioxy-N-methylamphetamine (MDMA) [94][95][96]. Therefore, the different impurities and intermediate chemicals can be identified and help understand the different synthetic routes in order to achieve a common source.…”
Section: Chemistry Of Illicit Drugsmentioning
confidence: 99%